Capitalism, culture, and decline in Britain, 1750-1990 - Rubinstein, W. D. (Routledge, 1993)
This original and controversial contribution to the topical debate on Britain's economic decline presents a critique of the thesis made familiar in recent years by Martin J. Wiener, Anthony Sampson, Correlli Barnett and others.